How Different Modes of Child Delivery Influence Abdominal Muscle Activities in the Active Straight Leg Raise - Kwon, Yu-Jeong (The Society of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to examine the activities of the abdominal muscles of women who had experienced vaginal delivery in comparison with those who had experienced Cesarean childbirth. [Subjects and Methods] A total of 14 subjects (7 vaginal delivery, 7 Cesarean section) performed an active straight leg raise to 20 cm above the ground, and we measured the activities of the internal oblique abdominal muscle, the external oblique abdominal muscle, and the rectus abdominal muscle on both sides using electromyography. The effort required to raise the leg was scored on a Likert scale. Then, the subjects conducted maximum isometric contraction for hip joint flexion with the leg raised at 20 cm, and maximum torque and abdominal muscle activities were measured using electromyography. [Results] During the active straight leg raise, abdominal muscle activities were higher in the Cesarean section subjects. The Likert scale did not show a significant difference. The activities of the abdominal muscles and the maximum torque of the hip joint flexion at maximum isometric contraction were higher in the vaginal delivery subjects. [Conclusion] The abdominal muscles of Cesarean section subjects showed greater recruitment for maintaining pelvic stability during the active straight leg raising, but were relatively weaker when powerful force was required. Therefore, we consider that more abdominal muscle training is necessary for maintaining pelvic stability of Cesarean section subjects.